Mecanical pathologies in lithic elements of the heritage churches in the Plaza Mayor de Cusco - Vargas Febres, Carlos (2021)
The aim was to categorize the pathologies of lithic elements and diagnose the level of existing damage caused by extrinsic and intrinsic agents on the facades of the Basilica-Cathedral Church and the Society of Jesus. The cross-sectional descriptive-level mixed approach was applied through direct observation. Seven lithic pathologies classified in the mechanical group were recorded (disintegration, cracks, fragmentation, perforation, missing, bursts, and erosion). Both churches have the presence of the same pathologies; because they share the same rock typology, as well as being exposed to the same environmental conditions. However, they also have a different orientation, which causes the level of aggression to be different.